Nahwu Shorof Teaching Method in Learning Arabic - Muliatno (Cattleya Darmaya Fortuna, 2023)
This article discusses the nahwu learning method. There are two general methods of teaching nahwu in Arabic. Given the importance of understanding nahwu science in learning Arabic, it was found that many students, even students of Arabic literature, did not even understand the rules in nahwu science, even though there was already learning nahwu science in compulsory subjects taught in class. This lack of understanding is due to several aspects, including: learning methods from lecturers which are sometimes not in accordance with the abilities of students and the large number of students majoring in Arabic literature with non-madrasa educational backgrounds who have never known Arabic. This causes delays in the process of learning and learning nahwu science in the classroom.